(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
In this paper, we introduce a new modified distribution called arcsine Rayliegh Pareto (ASRP) Distribution. We derived its mathematical and statistical properties, including survival function, hazard function, entropy, moment, moment generating function, and order statistics. We also used maximum likelihood estimation for estimating the parameters of the distribution. The plots of the cdf, pdf, hazard rate function, and survival function were illustrated with right skewed probability density function, cumulative distribution function with monotone increasing function, which converge at one. The value of some goodness of fit measure (i.e. AIC, AICc, and BIC) were computed, as well as the KS, A, and W statistic. Finally, we suggested that the new modified model outperform better than the other standard distribution using Carbon fibers data sets.